Optimalisasi Desentralisasi Fiskal di Indonesia Pasca Lahirnya Rezim Undang-Undang HKPD - Jauhar Nashrullah (Primagraha Law Review, 2023)
Birth of Law No. 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (HKPD Law) colors a new round of Fiscal Decentralization in Indonesia which in the last two decades has experienced ups and downs. This research is a type of normative research, the approach to be used is the statutory approach and the conceptual approach. Primary and secondary legal materials are collected through a literature study which will then be analyzed in a descriptive-qualitative manner and will later be outlined in the discussion description. The discussion results show that in the two decades of its implementation, fiscal decentralization has positively contributed to national development. However, several studies have also uncovered some negative developments. For this reason, in the context of accelerating development, improving, and responding to the challenges of the times, the HKPD Law was born. The substance of the HKPD Law is very positive in encouraging self-reliance and prosperity, starting from the reform of the tax and user fee system, and regional financing to central-regional synergy. In order to further optimize the HKPD Law, in the future several policy reforms are needed such as optimizing regional own-source revenues through wider tax decentralization, optimal utilization of regional financial loans, and involvement of law enforcement officials in TKDD supervision.